Blood on their hands : murder, corruption, and the fall of the Murdaugh dynasty - Matney, Mandy; Murnick, Carolyn (William Morrow, an imprint of HarperCollins Publishers, 2023)
"Years before the name Alex Murdaugh was splashed across every major media outlet in America, local South Carolina journalist Mandy Matney had an instinct that something wasn't right in the Lowcountry. The powerful Murdaugh dynasty had dominated rural South Carolina for generations. No one dared to cross them. When Mandy and her reporting partner Liz Farrell looked closer at a fatal boat crash involving the storied family's teenage son Paul, they began to uncover a web of mysteries surrounding the deaths of the Murdaughs' long-time housekeeper and a young man found slain years earlier on a backcountry road. Just as their investigations were unfolding, the brutal double murder of Maggie and Paul Murdaugh rocketed Alex Murdaugh onto the international stage"--